1791 Pa. Laws 105, ch. 1573, § 1, in Statutes at Large of Pennsylvania from 1682 to 1801 (Vol. 14, 1791-1793) - (:unkn) unknown (My University, 1791)
That it shall and may be lawful for the owners of gun-powder not deposited , or to be deposited, in the said magazine, the square to the south of Vine street, to remove and deposit the same in the said new magazine; and all gun-powder brought into the city of Philadelphia, from and after the first day of July next, shall be deposited and kept in the said new magazine subject to the regulation contained in the said first recited act.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER